(untitled) (Texas Journal of Multidisciplinary Studies, 2024)
The article discusses the legislative framework and practice of providing non-financial reporting on sustainable development in Uzbekistan, international guidelines and standards for disclosing ESG data, the importance of a universal reporting system for market development and attracting investments, and provides a conclusion and recommendations